Potential role of lipid peroxidation derived DNA damage in human colon carcinogenesis: studies on exocyclic base adducts as stable oxidative stress markers - Bartsch, Helmut; Nair, Jagadeesan (Cancer detection and prevention, 2002)
Molecular pathways to colorectal cancer involve multiple genetic changes that may be caused by overproduction of reactive oxygen species in cancer-related genes. Our aim was to investigate, whether besides direct oxidative DNA damage, reactive oxygen and nitrogen species induce lipid peroxidation (LPO) that could yield etheno-DNA adducts via trans-4-hydroxy-2-nonenal, a major aldehyde generated by LPO, in colon tissue. We analyzed the etheno-DNA adducts by a highly specific, ultrasensitive method involving immunoaffinity chromatography coupled with 32P-postlabelling [Carcinogenesis 16 (1995) 613] in affected colon epithelium from ulcerative colitis, Crohn’s disease and familial adenomatous polyposis (FAP) and compared them with asymptomatic colon tissue. In all these cancer prone colon tissues, the formation of markedly enhanced etheno adduct levels was demonstrated for the first time. Etheno-DNA adducts are promutagenic and cause genomic instability that could drive the inflamed colonic epithelia to malignancy. Etheno-DNA adducts appear promising biomarkers for (i) quantifying increased DNA damage in early stages of colon carcinogenesis and for (ii) verifying the efficacy of new antioxidants (e.g. [Lancet Oncol. 1 (2000) 107]) and chemopreventive agents in lowering oxidative stress and related cancer risk.
Gesehen am 12.01.2021